Optimal Siting and Sizing of Electric Vehicle Charging Stations and Distributed Generators in Distribution Systems by Meta Heuristic Techniques - Golive, Sai Goutham; Paramasivam, B.; Ravindra, J. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The augmented interest towards sustainable transportation initiatives has led to a substantial expansion of the transportation sector’s adaptation to electric vehicles (EVs). As the EV load cause an additional burden to the existing distribution system, may lead to the increase in actual power losses, a reduced voltage profile, and declined margins for voltage stability. In order to mitigate the impact of EV load on the Radial Distribution System (RDS), it becomes mandatory to strategically deploy Electric Vehicle Charging Stations (EVCSs) and Distributed Generators (DGs) at best locations within the system. The present study proposes an optimization technique with the simultaneous placement and sizing of EVCS and DG in the distribution systems. The problem at hand is framed with the objective of minimizing the real power losses and enhance the Voltage Stability Index (VSI) of the electrical distribution system using Grasshopper Optimization Algorithm. Simulation studies were conducted on the widely recognized IEEE 69-bus test systems in order to investigate and analyze the performance of the system.